Design and construction of a low cost solar TV transmitter - Chikwira, Cosmas (Midlands State University, 2018)
In Zimbabwe television (ZTV) transmission coverage is approximately 55% nationwide and is mainly confined to urban areas. The dissertation overviews activities of the author’s design of a solar tv transmitter prototype which will act as gap filler in remote areas where there is no television coverage. Due to recent progress in the field of Wireless Sensor Networks (WSN) in industry particularly for control and data processing, the same goal can be achieved in television broadcasting by harnessing this idea. Since WSN technology brings several advantages over traditional wired systems, including self-organization, rapid deployment, flexibility, and low power consumption this prompted the author to design the prototype. The prototype is going to be a completely self -contained outdoor unit with a battery backup which is recharged by a solar power unit. This will provide a complete solution to the Transmedia’s dilemma of the coverage increase of ZTV1 signals in a cost effective manner to most people who are information starved. The prototype is going to broadcast two channels so as to increase viewer’s choice. It can also be installed in colleges, rural community, or shopping malls where you can broadcast tutorial videos, entertainment and advertisements respectively. The design is going to implement digitilisation and analogue system so as to reduce cost and abide by International Telecommunication Union (ITU) digitalization deadline of June 15 2015.